TEKNIK PEMERIKSAAN BARIUM ENEMA PADA PASIEN ANAK DENGAN DENGAN KLINIS MORBUS HIRSCHPRUNG - Hartati, Sri; Yusda, Aldistira (JRI (Jurnal Radiografer Indonesia), 2021)
Background: Based on differences in theory with the field that focuses on 4 different factors, namely the use of Iodine contrast material which should be BaSO4 (Bontrager, 2012), the use of Nelaton Catheter which should be a Polycatheter or Barium set (Bontrager, 2012) and (Ballinger, 2012), the addition of Prone position on plain abdominal photo examination should only be in the Supine position, using the Oblique R / L position (Optional) which should only be plain AP photo, AP contrast, Lateral contrast, and AP Post evacuation (Bontrager, 2012) Methods: Qualitative descriptive, which is carried out by means of observation, interviews, literature review and documentation (photo taking), research This was carried out for 6 months with a total population of ten patients and a sample of three patients with details of one primary sample and two secondary samples. Results: Image analysis, and comparison of Barium Enema Pediatric examination techniques in the territory with the field obtained from interviews with three radiographers and three radiologists. Conclusions : The pediatric Barium enema examination technique is performed under fluoroscopy control with the ratio of contrast material to the liquid is 1: 4 and 1: 2 for Hirschprung Suspect and 2: 3 for clinical Morbus Hirschprung on Colostomy as well as AP and PA projection shooting techniques for preliminary photos, AP supine with contrast, lateral to contrast, and photographs 24 hours after examination (post evacuation).